Academic Librarians in Spanish-Speaking Latin America See a Growing Need for Librarian Role in Scholarly Publishing Literacy / Buitrago Ciro, J. (2022). How are academic libraries in Spanish-speaking Latin America responding to new models of scholarly communication and predatory publishing? Journal of Librarianship and Information Science, 54(3), 373–388. https://doi.org/10.1177/09610006211016533 - Lewis, Abbey (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2023)
Objective – To examine the current state of knowledge among academic librarians in Spanish-speaking countries in Latin America regarding open access and predatory publishing. Furthermore, the study sought to explore actions or potential plans among this group that could allow them to better assist researchers with these aspects of scholarly publishing literacy.Design – An online survey, followed by interviews with self-selected participants.Setting – Academic libraries in Spanish-speaking countries in Latin America.Subjects – 104 librarians in the online survey and seven librarians in the interviews, each holding a position in an academic library in Spanish-speaking Latin America.Methods – An anonymous survey in Spanish consisting of 34 required questions was built with SurveyMonkey and distributed to participants between 30 July 2020 and 20 September 2020. Survey respondents were directed to contact the author via email if they wished to participate in follow-up interviews. Interviews were then conducted in Spanish over Zoom between 10 October 2020 and 10 November 2020, and the transcripts were coded and analyzed with NVivo.Main Results – Of the survey’s respondents, 31.73% indicated that their library has a scholarly communication librarian, 29.81% noted that the library receives requests for assistance with finding journals in which to publish at least once per week, and 16.35% reported this type of request at least 1-2 times per month. In specific regard to predatory publishing, almost 52.88% of respondents indicated that they never receive questions on this topic, and 25.00% answered that users seek this kind of information less than once per month. Additionally, 31.73% responded that information on predatory publishing is not available at their library, and 42.31% rated their own knowledge of predatory publishing as fair to very poor. Finally, 44.23% reported plans to develop training or information to educate their institution’s research communities about predatory publishing, and 2.88% planned to recruit a scholarly communications specialist. In interviews, all participants agreed that exchanging information with other institutions with more knowledge and services related to predatory publishing would be beneficial. Three interviewees saw a general role for the library in providing information on predatory publishing, and three others indicated that this should be a leadership role when working in conjunction with other departments. All participants saw a lack of knowledge about predatory publishing as one of the primary difficulties for academic libraries, and three reported that the survey itself had led them to recognize the importance of the library’s role in scholarly communication literacy and create plans for their library to assist researchers in regard to predatory publishing.Conclusion – Academic libraries in Spanish-speaking countries in Latin America are not yet offering robust support for researchers concerning predatory publishing, but there is growing recognition of the issue, as well as interest in further developing expertise among librarians. Collaboration and exchanges of information with other institutions with more developed resources related to predatory publishing is viewed positively and may build upon existing knowledge of open access publishing.